Overnight-Intraday Mispricing of Chinese Energy Stocks: A View from Financial Anomalies - Zhou, Min; Liu, Xiaoqun (Frontiers in Energy Research, 2022)
We verify the existence of firm-level “intraday return versus overnight return” pattern and overnight-intraday effect of nine financial anomalies in Energy industry stocks of Chinese stock market. Though energy finance has been an independent research area, we also take A-shares stocks as samples for empirical analysis to avoid the so-called sample selection bias. Specifically, it verifies that the overnight returns are strongly negative and intraday return are positive in Energy industry stocks, which is totally contrary to the American stock markets. In addition, unlike Lou et al. (2019), alphas of the zero-cost strategies based on 9 classic financial anomalies are almost earned at night for Energy industry stocks. Finally, it is risk-related anomalies that occur during overnight for Energy industry stocks, while both four risk-related anomalies and two firm characteristics related anomalies occur at night for all A-shares stocks. Our empirical findings based on Chinese financial markets enrich the existing research on the mispricing of financial anomaly and shed a new sight on the asset pricing in Energy finance.